1998
DOI: 10.1006/jmbi.1998.1625
|View full text |Cite
|
Sign up to set email alerts
|

The solution structure of a fungal AREA protein-DNA complex: an alternative binding mode for the basic carboxyl tail of GATA factors 1 1Edited by P. E. Wright

Abstract: The solution structure of a complex between the DNA binding domain of a fungal GATA factor and a 13 base-pair oligonucleotide containing its physiologically relevant CGATAG target sequence has been determined by multidimensional nuclear magnetic resonance spectroscopy. The AREA DNA binding domain, from Aspergillus nidulans, possesses a single Cys 2 -Cys 2 zinc ®nger module and a basic C-terminal tail, which recognize the CGATAG element via an extensive network of hydrophobic interactions with the bases in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 49 publications
1
91
0
Order By: Relevance
“…Shown are electrophoretic mobility shift assays comparing the binding specificities of peptides CC14 (D) and CC13 (E) for various dsDNA oligomers, corresponding to data presented in A and C, respectively. the recognition of the GAT motif, in a manner similar to the corresponding PL-RR residues of the AREA zinc finger (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Shown are electrophoretic mobility shift assays comparing the binding specificities of peptides CC14 (D) and CC13 (E) for various dsDNA oligomers, corresponding to data presented in A and C, respectively. the recognition of the GAT motif, in a manner similar to the corresponding PL-RR residues of the AREA zinc finger (12).…”
Section: Discussionmentioning
confidence: 99%
“…Shown are sequences of the N-terminal and C-terminal zinc finger peptides described in this study with modified or additional residues highlighted in bold black characters. Residues indicated in red represent the zinc chelating CXXC, whereas residues highlighted in bold blue characters represent the core zinc finger residues responsible for the recognition of the GAT DNA motif (11,12). The region encompassing the single ␣-helix of the core finger is underlined.…”
Section: Binding Site Selections Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Structural studies have shown that NmrA binds directly to the zinc finger of AreA mainly through interactions with alpha helices 1, 6, and 11, and amino acid substitutions in alpha helix 6 (E193Q/D195N or Q202E/ F204Y) reduce the affinity of this interaction. 9,11 Comparison with a nuclear magnetic resonance solution structure of the AreA Zf in a complex with a GATAcontaining double stranded oligonucleotide 19,20 shows parts of helices a-6 and a-11 of NmrA are positioned close to the GATA motif in the DNA, mimicking the major groove of the DNA. 9 We show here for the first time that A. nidulans has three protease activities that digest NmrA(Mr 38.8 kDa) in an ordered manner to generate an N-terminal protease resistant 32 kDa fragment and that in vitro the presence of oxidized dinucleotides substantially enhances the resistance of this N-terminal fragment to further digestion by these proteases.…”
Section: Introductionmentioning
confidence: 99%